The axial pelvic rotation assessment based on pelvic bones according to the original radiographic method using a pelvis 3D model - Černý, Pavel; Mařík, I (Pohybové ústrojí. Pokroky ve výzkumu, diagnostice a terapii, 2015)
The goal of the prospective study is to assess pelvic rotation with the use of a new radiographic method based on determination of pre-defined points on an anterior-posterior (AP) X-ray projection of the pelvis. The authors have already described and published an original radiographic method of assessing axial pelvic rotation based on the position of the sacrum, the shadows of the pelvis inlet and the symphysis position. Not all X-ray images capture the entire pelvis, which makes it impossible to read the symphysis position and use the original method. However, most X-ray images portray complete iliac wings, for which reason this study attempts to find geometric relations of the wings projections in the case of axial pelvic rotation. The new radiographic method is based on reading the width of the shadows or iliac wings and allows for determination of geometric value of the axial pelvic rotation based on a simple principle by means of direct measurement of the relevant angle by a protractor. No special tools are needed, the axial pelvic rotation can be measured both on a conventional image and on a digital image. The presented method can be easily implemented into computer programs where only two relevant abscissae are constructed and the angle is then calculated automatically based on the scheme. This simple method can be used for X-ray assessment of pelvic rotation for many other reasons in many different fields (e.g. anthropology, biomechanics, X-ray analysis, paediatric orthopaedics, orthopaedic prosthetics, spondylology, surgery for spondylosis, etc.).
Keywords: Spinal Curvatures; Pelvis; zakřivení páteře; rotace; lidé; Rotation; prospektivní studie; radiografie; Radiography; Prospective Studies; skolióza; Scoliosis; pánev; Humans